2021
DOI: 10.1155/2021/9511772
|View full text |Cite
|
Sign up to set email alerts
|

AMH Is a Good Predictor of Metabolic Risk in Women with PCOS: A Cross-Sectional Study

Abstract: Objective. The relationship between metabolic risk and ovarian function is ambiguous. This retrospective study analyzed the medical records of 461 PCOS patients collected between January 2019 and June 2020 to investigate the relationship between serum anti-Müllerian hormone (AMH) and parameters of metabolic risk in the population with polycystic ovary syndrome (PCOS). Methods. A total of 461 PCOS patients aged 20–40 years were included and stratified into four groups according to the AMH level. The association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…A recent study found a strong link between AMH and metabolic syndrome, but not with BP. 26 However, that study excluded patients with obesity. Our study's principal limitations were the limited number of patients and the use of only OV criteria assessed by different routes and sonologists.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found a strong link between AMH and metabolic syndrome, but not with BP. 26 However, that study excluded patients with obesity. Our study's principal limitations were the limited number of patients and the use of only OV criteria assessed by different routes and sonologists.…”
Section: Discussionmentioning
confidence: 99%
“…A dysfunction in the immune system affects follicular development or ovulation [ 31 ]. On the other hand, an increase in inflammatory factors in PCOS patients changes the level of AMH, resulting in glucose and lipid metabolism disorder [ 32 , 33 ]. This disorder increases the risk of IR and synthesis of androgens, destroying normal ovulation and fertilization in women.…”
Section: Discussionmentioning
confidence: 99%
“…(Teede et al, 2019;Shrikhande et al, 2020;Vatansever et al, 2020). AMH supplementation is able to maintain follicular reserve in some ovarian injury models, such as chemotherapy-induced premature ovarian failure, polycystic ovary syndrome (PCOS) (Sonigo et al, 2019;Hoyos et al, 2020;Ou et al, 2021;Rudnicka et al, 2021).…”
Section: Amhmentioning
confidence: 99%